2007
DOI: 10.1007/s00431-007-0515-y
|View full text |Cite
|
Sign up to set email alerts
|

Central precocious puberty due to hypothalamic hamartoma in a 7-month-old infant girl

Abstract: Hypothalamic hamartomas (HH) are rare congenital lesions of the tuber cinereum presenting with the classic triad of gelastic epilepsy, central precocious puberty (CPP) and developmental delay. In light of the important and diverse consequences of precocious puberty for affected children and their families, a correct diagnosis without delay is imperative. We present here a rare case of a 7-month-old infant girl with CPP and HH who was successfully treated with depot gonadotropin-releasing hormone (GnRH) analogu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…The underlying disease of the youngest boy presenting with CPP in our study was a hypothalamic hamartoma, which was reported previously in a 7-month-old infant with PP24). Hypothalamic hamartoma was the most commonly identified CNS lesion in previous studies whereas in our study, optic glioma and obstructive HCP were the most common lesions in CPP patients.…”
Section: Discussionsupporting
confidence: 69%
“…The underlying disease of the youngest boy presenting with CPP in our study was a hypothalamic hamartoma, which was reported previously in a 7-month-old infant with PP24). Hypothalamic hamartoma was the most commonly identified CNS lesion in previous studies whereas in our study, optic glioma and obstructive HCP were the most common lesions in CPP patients.…”
Section: Discussionsupporting
confidence: 69%
“…3,102 However, medical therapy in which long-acting GnRH analogs such as leuprolide acetate are used is now the primary treatment for most patients with HH-related CPP. 20,93 Although the majority of HHs can be easily classified as either sessile or pedunculated, some intermediary forms have been described. For example, a large sessile HH that has a broad attachment to the base of the hypothalamus and extends into the interpeduncular cistern may have features of both sessile and pedunculated HHs.…”
Section: Topological Classificationmentioning
confidence: 99%
“…All these findings are characteristic of GDPP or central precocious puberty 12 .MRI is the primary imaging modality for detection of Hypothalamic hamartomas allowing better tissue characterization and greater anatomic details 12 .The imaging features most commonly consist of a hypothalamic mass isointense to grey matter on T1W sequence, and increased signal intensity on T2W and FLAIR (fluid attenuated inversion Recovery) sequence 8 .The MRI of our patient revealed all of these features.…”
Section: Discussionmentioning
confidence: 58%